Sport and the LGBTIQ+ Community: A South Australian Study - Drummond, Murray; Elliott, Sam; Drummond, Claire; Prichard, Ivanka; Lewis, Lucy; Bevan, Nadia (Frontiers in Psychology, 2021)
This is a paper based on research with the LGBTIQ+ community in South Australia, the likes of which has not been conducted previously in the state. The paper, which utilized both quantitative (n=148) and qualitative (n=31) research methods identifies the key issues that the LGBTIQ+ community face with respect to sporting involvement. There were a range of themes that emerged in relation to a variety of topics including homophobia, sexism and gender discrimination, gender roles and gender stereotypes. This paper provides data and discussion around this important part of the research, which has implications pertaining to sporting organizations and the LGBTIQ+ community